Mismatch Negativity in Childrenwith Cochlear Implant - Fernandes,Natalia Martinez (2019)
Abstract Introduction The mismatch negativity (MMN) is a negative long-latency auditory potential elicited by any discriminable change in a repetitive aspect of auditory stimulation. This evoked potential can provide cortical information about the sound processing, including in children who use cochlear implants. Objective To identify MMN characteristics regarding latency, amplitude, and wave area in cochlear implanted children and to identify associations among language development, speech perception and family involvement. Methods This is a descriptive, observational, cross-sectional study, which compared two groups: study group-children with cochlear implant, and control group-hearing children. The children were submitted to MMN evaluation with non-verbal tone burst stimulus, differing in frequency in sound field at 70 dBHL, with SmartEP equipment (Intelligent Hearing Systems, Miami, FL, USA). Speech perception and language development questionnaires were also applied, and the family participation in the rehabilitation process was classified. Results The occurrence ofMMNwas 73.3% for the control group and 53.3% for the study group. Values of latency, amplitude and area of MMN of children using cochlear implants were similar tothose ofhearingchildren, anddidnot differbetweengroups. The occurrence of MMN was not correlated to the variables of hearing, language and family categories. Conclusion Children with cochlear implants showed similar MMN responses to those of the children in the control group, withmean latency, amplitude andarea of 208.9ms (±12.8), -2.37 μV (±0.38) and 86.5 μVms (±23.4), respectively. There was no correlation between the presence of MMN and children’s performance in the auditory and language development tests or family involvement during rehabilitation.